2015
DOI: 10.1109/tnet.2014.2306416
|View full text |Cite
|
Sign up to set email alerts
|

Practical Conflict Graphs in the Wild

Abstract: Abstract-Today, most spectrum allocation algorithms use conflict graphs to capture interference conditions. The use of conflict graphs, however, is often questioned by the wireless community for two reasons. First, building accurate conflict graphs requires significant overhead, and hence does not scale to outdoor networks. Second, conflict graphs cannot properly capture accumulative interference. In this paper, we use large-scale measurement data as ground truth to understand how severe these problems are and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Moreover, most of these studies consider that nodes (or links), that are identified in conflict, are permanently in conflict, which is not true as shown in the previous section. This is for instance the case in [11,13,15].…”
Section: State-of-the-artmentioning
confidence: 91%
“…Moreover, most of these studies consider that nodes (or links), that are identified in conflict, are permanently in conflict, which is not true as shown in the previous section. This is for instance the case in [11,13,15].…”
Section: State-of-the-artmentioning
confidence: 91%
“…To the best of our knowledge, no previous works have dealt with large datasets’ analysis, corresponding to the conflict graphs of real-world Wi-Fi networks and its evolution over time. In [ 35 ], the authors addressed problems related to the construction of the conflict graphs using measurement-calibrated propagation models in order to avoid the need for detailed signal measurements (see later in Sect. 3 the detail about what Cisco does [ 36 ]).…”
Section: Related Workmentioning
confidence: 99%
“…As nodes in a WMN can have several radio interfaces, the conflict graph takes into account the presence of several antennas/radios. The authors of Reference 8 also propose a new conflict graph that is able to represent interference between APs but also cumulative interference coming from several neighboring APs transmitting at the same time. In Reference 9, the authors assess interference between nodes through a set of received signal strength (RSS) measurements.…”
Section: State Of the Artmentioning
confidence: 99%